Mental health assessment among staff working in an institution in Kuantan, Pahang, Malaysia: does designation of workplace determine it - Abdullah, Fa’iza; Tin, Myo Han; Swe, Swe Latt; Md Aris, Mohd Aznan; Halim, Noor Azlina; Abdullah, Noraini; Omar, Mohd Faizul (Academy of Family Physicians of Malaysia and Family Medicine Specialist Association, 2015)
The prevalence of work-related mental health problem is increasing trends in Malaysia. Among adult population, 12% suffered mental illness such as anxiety, stress,depression and schizophrenia. Majority of them are still working. Mental health assessment among staff is an entry point in providing appropriate mental health care to reduce mental health illness and its related social and behavior problems.